Profile of the centrality of work in Mexico based on the world values survey 2017-2020 - Carlos Mejía Reyes (Universidad Central de Venezuela, 2021)
The centrality of work is defined as the set of beliefs, definitions, and value that individuals and groups attribute to work; which depends, from a quantitative perspective, on macroeconomic factors such as wealth distribution and human development; as well as control variables of type of work, education, age, among others. Thus, the objective of this document is to expose the statistical behavior of the centrality of work in Mexico. It is based on the World Values Survey, emphasizing the review in the period 2017 -2020, to outline an overview from a cross-sectional review or prevalence, compared with other countries and spheres of life, in correlation with elementary structural and sociodemographic variables. The main results show that work is very important in Mexico compared to other countries and is one of the most valued areas of life, only below the family. The reasons for the valuation are explained by the shortage of material benefactors that induce to estimate the activity with the instrumental objective of satisfying elementary needs. However, the variables associated with high valuation are simplified in better occupational and vocational training situations.  Key words: Work; Centrality of work; meanings of work; Mexico